2012
DOI: 10.5402/2012/835391
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Extraction from Malaysian Cultured Catfish (Hybrid Clarias Sp.): Kinetics and Optimization of Extraction Conditions Using Response Surface Methodology

Abstract: A central composite design (CCD) was used for the experimental design and results analysis to obtain the optimal processing parameters (acetic acid concentration, liquid to solid ratio, and stirring speed) for the extraction of pepsin soluble collagen (PSC) from muscles of cultured hybrid catfish of Clarias sp. (Clarias gariepinus ×C. macrocephalus). Statistical analysis showed that the linear and quadratic terms of these three independent variables had significant effects on the yield of PSC. There was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(52 reference statements)
2
8
0
Order By: Relevance
“…1). The results of this work confirmed previous reports by Kiew and Don (2012) and Wang et al (2008), who concluded that collagen can be extracted more efficiently from cultured catfish and grass carp by extending the treatment time and stirring speed. However, longer extraction durations require higher expenditures of energy.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1). The results of this work confirmed previous reports by Kiew and Don (2012) and Wang et al (2008), who concluded that collagen can be extracted more efficiently from cultured catfish and grass carp by extending the treatment time and stirring speed. However, longer extraction durations require higher expenditures of energy.…”
Section: Resultssupporting
confidence: 92%
“…A greater solubility of the eggshell membrane in acetic acid was observed, thereby exhibiting a higher potential for collagen's particles to be extracted from the eggshell membrane and to enter the medium. A further increase in the speed, making it faster than 400 rpm, however, failed to yield substantial improvements regarding extraction results (Kiew and Don, 2012). Extraction time and yield correlated positively (Figs.…”
Section: Resultsmentioning
confidence: 97%
“…The R 2 of Eq. (9) was 0.982, indicating a close agreement between the experimental results and values predicted by the statistical model (Kiew and Mat Don, 2012). The error analysis indicated that the coefficient of variation was 1.16%, confirming the validity of the model for the level of confidence employed (Gunst et al, 2006).…”
Section: Statistical Effects Of the Factors On The Response Variablessupporting
confidence: 66%
“…The SNT free of NCP, obtained under optimal conditions, was subjected to extraction with 0.7 M acetic acid (40 mLg -1 ), stirring at 70 rpm during 5 h ( (Kiew and Mat Don, 2012). The extraction was performed at 20 C because the properties of obtained collagen exhibited non-significant differences with those of the collagen obtained at lower temperatures (Potaros et al, 2009).…”
Section: Conditions Of Acid Extraction Of Collagenmentioning
confidence: 99%
See 1 more Smart Citation